Analisis kesalahan Siswa SMP dalam Memecahkan Masalah Kontekstual pada Materi Perbandingan Ditinjau Dari Gaya Kognitif - Mufidatin Anjelina; Ismail Ismail (Program Studi S1 Matematika UNESA, 2023)
The aim of this research is describe errors conducted by students of junior high schools with cognitive styles type field-dependent and field-independent in solving contextual problems in proportion and its causal factors. This research is a descriptive qualitative research. The research subjects for this research were 2 students with the most errors from each type of cognitive styles. The two subjects are of the same gender. Data was collected by interview techniques and test. This research used 3 kinds of instruments, those were interview guidelines, the GEFT test, and diagnostic tests. Data of this research is processed using Miles and Huberman technique which includes 3 steps. The results of this research shows the errors made by subject FD and FI cognitive style, and also the factors that cause the errors. Subject with FD cognitive style made errors such as, errors in understanding the problem, erros in devising a plan, erros in carrying out the plan, and looking back errors. The errors made by students with FI cognitive style included carrying out plans, and checking again. Factors that cause subject that has FD cognitive style made errors tend to be caused by difficulties in understanding problems, lack of the understanding of the mathematical concepts, and also lack of calculating skills. Factors that cause subject that has FI cognitive style made errors tend to result from a lack of thoroughness in students when solving problems.